2021
DOI: 10.3390/ijms22094963
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Intrinsic Muscle Weakness on Muscle–Bone Crosstalk in Osteogenesis Imperfecta

Abstract: Bone and muscle are highly synergistic tissues that communicate extensively via mechanotransduction and biochemical signaling. Osteogenesis imperfecta (OI) is a heritable connective tissue disorder of severe bone fragility and recently recognized skeletal muscle weakness. The presence of impaired bone and muscle in OI leads to a continuous cycle of altered muscle–bone crosstalk with weak muscles further compromising bone and vice versa. Currently, there is no cure for OI and understanding the pathogenesis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 123 publications
0
7
0
Order By: Relevance
“…Previous studies have reported that upper-extremity deformities affect the performance of basic self-care tasks and impact mobility, transfers, and ambulation, especially in children with severe OI [ 27 ]. Moreover, patients with OI have a low muscle size [ 12 , 28 ], lower limb muscle weakness [ 12 , 29 , 30 , 31 , 32 , 33 , 34 ], restricted joint range of motion [ 32 , 35 ], pain [ 36 , 37 ] and fear of fractures when bearing weight [ 36 , 38 ]; all of which could cause obstacles in accomplishing these daily tasks and have a great impact on the functional independence of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that upper-extremity deformities affect the performance of basic self-care tasks and impact mobility, transfers, and ambulation, especially in children with severe OI [ 27 ]. Moreover, patients with OI have a low muscle size [ 12 , 28 ], lower limb muscle weakness [ 12 , 29 , 30 , 31 , 32 , 33 , 34 ], restricted joint range of motion [ 32 , 35 ], pain [ 36 , 37 ] and fear of fractures when bearing weight [ 36 , 38 ]; all of which could cause obstacles in accomplishing these daily tasks and have a great impact on the functional independence of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…(6)(7)(8)(9) Although physical activity is shown to be one of the major determinants of bone mass and resistance to fractures in a healthy population, studies evaluating bone parameters in OI did not take physical activity into account. (10,11) Therefore, the association of physical activity with bone parameters in OI remains currently unclear.…”
Section: Introductionmentioning
confidence: 99%
“…(16,17) In children with OI, conflicting results, ranging from reduced to normal biomechanical responsiveness, have been reported. (4,10,14) Exploring this relationship between muscle and bone is of clinical importance, as it permits to assess whether muscle-centered therapeutic strategies (eg, exercise, muscle strengthening, and whole-body vibration therapy) could improve bone strength in OI. (10,14,18) However, to our knowledge, no studies have evaluated the association between muscle and bone parameters in adults with OI type I.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations